Functional expression of bradykinin B1 and B2 receptors in neonatal rat trigeminal ganglion neurons - Kawaguchi, Aya; Sato, Masaki; Kimura, Maki; Yamazaki, Takaki; Yamamoto, Hitoshi; Tazaki, Masakazu; Ichinohe, Tatsuya; Shibukawa, Yoshiyuki (Frontiers in Cellular Neuroscience, 2015)
Bradykinin (BK) and its receptors (B1 and B2 receptors) play important roles in inflammatory nociception. However, the patterns of expression and physiological/pathological functions of B1 and B2 receptors in trigeminal ganglion (TG) neurons remain to be fully elucidated. We investigated the functional expression of BK receptors in rat TG neurons. We observed intense immunoreactivity of B2 receptors in TG neurons, while B1 receptors showed weak immunoreactivity. Expression of the B2 receptor colocalized with immunoreactivities against the pan-neuronal marker, neurofilament H, substance P, isolectin B4, and tropomyosin receptor kinase A antibodies. Both in the presence and absence of extracellular Ca2+ ([Ca2+]o), BK application increased the concentration of intracellular free Ca2+ ([Ca2+]i). The amplitudes of BK-induced [Ca2+]i increase in the absence of [Ca2+]o were significantly smaller than those in the presence of Ca2+. In the absence of [Ca2+]o, BK-induced [Ca2+]i increases were sensitive to B2 receptor antagonists, but not to a B1 receptor antagonist. However, B1 receptor agonist, Lys-[Des-Arg9]BK, transiently increased [Ca2+]i in primary cultured TG neurons, and these increases were sensitive to a B1 receptor antagonist in the presence of [Ca2+]o. These results indicated that B2 receptors were constitutively expressed and their activation induced the mobilization of [Ca2+]i from intracellular stores with partial Ca2+ influx by BK. Although constitutive B1 receptor expression could not be clearly observed immunohistochemically in the TG cryosection, cultured TG neurons functionally expressed B1 receptors, suggesting that both B1 and B2 receptors involve pathological and physiological nociceptive functions.